STRATEGI PEMASARAN SEMEN INDONESIA SIG UNTUK MEMPERTAHANKAN MARKET SHARE SEMEN BAG DI JAWA TIMUR - Abdul Bari; Rahmah; Fitriani; Fitriyatus Solikhah; Hotim; Holifatur Rohmah; Museiyanah; Nur Azizah; Nurhalimah (ICO EDUSHA, 2022)
Marketing strategy is one way to win a sustainable competitive advantage for companies that produce goods or services. The marketing strategy can be seen as one of the bases used in preparing the company's overall planning. In view of the extent of the problems that exist within the company, it is necessary to have a comprehensive plan to serve as a guideline for the company segment in carrying out its activities. Another reason that shows the importance of a marketing strategy is the increasingly fierce competition in companies in general. This study aims to get an overview of the marketing strategy to increase competitiveness, and to find out how effective the implementation of the marketing strategy has been. This research was conducted at PT. Semen Indonesia, Tuban. Data collection techniques with documentation, interviews and observations, this type of research is descriptive. The results of the analysis of the effectiveness of the marketing strategy show that there is an increase in competitiveness from year to year and SIG is used as a reference for the effectiveness of marketing strategies in competition between cement companies. Keywords: Marketing strategy, planning and Competitiveness   REFERENSI Cakti Indra Gunawan dan Liva Puspita Anggraini, “The Analisis Of Strategic Management: Comparation Between Strategic Management Of  PT. Semen Indonesia tbk And Pt.Holcim Indonesia tbk”, Jurnal Ilmu Manajemen Dan Akuntansi, Volume 3, Nomer 2 (2015), 14. SIG, “Membangun Kehidupan Berkelanjutan Untuk Generasi Mendatang”, dalam https://sig.id/id/profil-perusahaan/ (2020). Estu Suryowati, “Berubah Jadi SIG, Ini Maksud Rebranding Semen Indonesia”  Jawa Pos  (12 Februari 2020). Kholida qothrunnada, “Pengertian Strategi Pemasaran: Tujuan, Fungsi, Elemen, dan Contohnya”, dalam https://finance.detik.com/berita-ekonomi-bisnis/d-6011378/pengertian-strategi-pemasaran-tujuan-fungsi-elemen-dan-contohnya  (01 Apr 2022) . Kunaifi, Aang. Manajemen Pemasaran Syari’ah Pendekatan Human Spirit; Konsep, Etika, Strategi, dan Implementasi. 1 ed. Vol. 1. 1 1. Yogyakarta: Maghza Pustaka, 2016. Moh Rusdi,”Strategi Pemasaran Untuk Meningkatkan Volume penjualan Perusahaan Genting UD. Berkah Jaya”, Jurnal Studi manajement Dan Bisnis, Volume 6 (2) 2019, 52. Dayat, “Srtategi Pemasaran Dan Optimalisasi Bauran Pemasaran Dalam Merebut Calon Konsumen Jasa Pendidikan”, Jurnal Mu’allim, Volume 1 Nomer 2 (juli 2019). Saputra, Taufik Aris, Aang Kunaifi, Dan Siti Azizah. “Diversifikasi Produk Pendekatan Islamic Ethic Dalam Meningkatkan Omset Bisnis Retail.” Cendekia : Jurnal Studi Keislaman 7, No. 1 (2021): 1–16. Sigit Wahono,”Strategi Komunikasi PT. Semen Indonesia (persero) tbk Dalam Manajemen Isu Pembangunan Pabrik Rembang “, Jurnal Ilmu Komunikasi, Volume 3, Nomer 2 (Agustus 2020), 5.